Starvation‐induced MTMR13 and RAB21 activity regulates VAMP8 to promote autophagosome–lysosome fusion. (3rd February 2015) - Jean, Steve; Cox, Sarah; Nassari, Sonya; Kiger, Amy A
Abstract Autophagy, the process for recycling cytoplasm in the lysosome, depends on membrane trafficking. We previously identified Drosophila Sbf as a Rab21 guanine nucleotide exchange factor (GEF) that acts with Rab21 in endosomal trafficking. Here, we show that Sbf/MTMR13 and Rab21 have conserved functions required for starvation‐induced autophagy. Depletion of Sbf/MTMR13 or Rab21 blocked endolysosomal trafficking of VAMP8, a SNARE required for autophagosome–lysosome fusion. We show that starvation induces Sbf/MTMR13 GEF and RAB21 activity, as well as their induced binding to VAMP8 (or closest Drosophila homolog, Vamp7). MTMR13 is required for RAB21 activation, VAMP8 interaction and VAMP8 endolysosomal trafficking, defining a novel GEF‐Rab‐effector pathway. These results identify starvation‐responsive endosomal regulators and trafficking that tunes membrane demands with changing autophagy status.